The Effect of Caricature Media on Poetry Writing Ability of Grade VII Students in SMP 08 Muhammadiyah Medan - Hasibuan, Irfan (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
The aim of this research is to see the influence of caricature drawing media on the ability to write poetry to improve the poetry writing ability of class VII junior high school students. The type of research used in this research is a type of method. This research is quantitative research using the experimental method Posttest only control design, where in this design there are two groups, each of which is chosen randomly (R). the first group was given treatment (X) and the other group was not. This research was carried out at SMP 08 Muhmammadiyah Medan. The sampling technique used in this research was random sampling by selecting two classes from three classes. The results obtained from the random process were class VII-A with a total of 28 students and class VII-B with a total of 33 students as samples in the research with a total of 61 students. With different basic abilities, students in the research sample will receive the same rights, namely the initial test and the final test. The results obtained from the random process were class VII-B with 33 students as the experimental class and class VII-A with 28 students as the control class. Based on the results of research data analysis, it shows that the use of caricature image media provides better results in the evaluation of poetry writing ability tests by Class VII students of SMP Muhammadiyah 08 Medan for the 2019-2020 learning year compared to learning without using caricature image media. Keywords: Image Media, Writing Ability, Poetry